The Waite Group's object-oriented programming in C++ - Lafore, Robert (Waite Group Press, 1995)
Includes examples like: ELEV, VERYLONG, and PIPES; Covers the features of the C++ programming language including templates and exceptions; Fully compatible with Borland C++ 4.5 compilers